Pembelajaran Kontekstual untuk Meningkatkan Kemampuan Peserta Didik Menulis Teks News Items - Umi Fadhilah (EduInovasi: Journal of Basic Educational Studies, 2022)
This research is an effort to improve the quality of English learning through a contextual approach to improve the ability of students to write news items text at SMK Negeri 2 Depok City. The purpose of this study was to apply the steps in the learning model using a contextual approach to improve the ability of students to write news items texts for class XII students of Tourism at SMK Negeri 2 Depok City, with constraints and solutions. This research is a collaborative Classroom Action Research (CAR) carried out in two cycles, each cycle includes the stages of planning, implementation, observation and reflection. The subjects of this study were students of class XII Tourism. The results showed that the use of a contextual approach could improve students' ability in writing news items text for students of Class XII Tourism at SMK Negeri 2 Depok City. In the learning process cycle I to cycle II the increase in success in the second cycle the average value reached 7.9 from the average value of 6.3 in the first cycle. Keywords: Contextual learning, Ability to write news items text.